Relation About People’s Perception Between open defecation free And Bowel Habit Puskesmas Mundu Kabupaten Cirebon - Dina Viyata Agustin; Lili Amaliah; Andinna Ananda Yusuff (Jurnal Kesehatan Mahardika, 2020)
The behavior of open defecationis a habit or practice of everyday culture of the people who still dispose of poop or stool in an open place. The annual report of the Mundu Community Health Center in 2018, for the environmental health program in the STBM activities, can be identified by the ODF verified village by 0.00% or there is still no village categorized as ODF village which currently still has many people defecating carelessly in the work area Mundu Health Center although the implementation of the STBM program has been done 100%. The result of the research showed that mostdetermine the relationship between community perceptions of ODF and open defecationin the work area of Mundu Health Center, Cirebon Regency.The research method used is quantitative with cross Sectional Study design. The population in this study were all communities residing in the work area of Mundu Health Center, Cirebon Regency. The sample in this study used a purposive sample which amounted to 100 respondents during the month of July 2019.The results showed that there was a significant relationship between community perceptions of ODF and BABS habits in the work area of Mundu Public Health Center, Cirebon Regency, namely ρ value 0.01 with a value of α <0.05, which means 0.01 <0.05.Providing information education to the public about the effects of any defecation can change people's perceptions of ODF to be good so that it can increase public awareness of BABS habits.